2023
DOI: 10.1097/md.0000000000035183
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the development of postoperative atrial fibrillation after esophagectomy for esophageal cancer

Feng He,
Xi Wu,
Ziheng Yang
et al.

Abstract: Postoperative atrial fibrillation (POAF) is one of the most complications after esophagectomy. Thus, our study was conducted to explore risk factors that are associated with POAF following esophagectomy. In the current study, we retrospectively evaluated 511 patients with esophageal cancer who underwent esophagectomy at our center between May 2018 and December 2020. The incidence of POAF and clinical variables were collected and analyzed. POAF occurred in 62 (12.13%) of 511 patients. Increasing age (P = .004) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It is generally known that older patients have poorer physical condition and are more likely to suffer from chronic diseases such as malnutrition, diabetes mellitus, coronary artery disease, and hypertension, and that these underlying diseases increase the risks associated with esophageal cancer surgery. 11 Age is one of the major risk factors for the development of atrial fibrillation in patients undergoing esophagectomy, according to a study by He et al 12 Another study revealed a substantial rise in the occurrence of postoperative bedsores, depression, confusion, and malnutrition in elderly patients who underwent gastrointestinal surgery. 13 Consequently, when confronted with heightened surgical threats and complications, elderly patients usually opt for more cautious treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally known that older patients have poorer physical condition and are more likely to suffer from chronic diseases such as malnutrition, diabetes mellitus, coronary artery disease, and hypertension, and that these underlying diseases increase the risks associated with esophageal cancer surgery. 11 Age is one of the major risk factors for the development of atrial fibrillation in patients undergoing esophagectomy, according to a study by He et al 12 Another study revealed a substantial rise in the occurrence of postoperative bedsores, depression, confusion, and malnutrition in elderly patients who underwent gastrointestinal surgery. 13 Consequently, when confronted with heightened surgical threats and complications, elderly patients usually opt for more cautious treatment options.…”
Section: Discussionmentioning
confidence: 99%